1H-NMR analysis of amino acid metabolism in aqueous humor of patients with cataract, according to diabetes status. Issue 6 (June 2020) - Jin, Jing; Sun, Qian; Wu, Zan; Liu, Kun; Song, Zhengyu; Su, Li
Objective: To investigate the differences in amino acid metabolism in aqueous humor of patients with cataract, according to diabetes status, using a 1 H-nuclear magnetic resonance approach. Methods: Aqueous humor samples from patients with age-related cataract, with or without diabetes, were collected during cataract surgery. All samples underwent nuclear magnetic resonance spectra analysis to characterize their metabolic function. Potential metabolic pathways were analyzed via MetaboAnalyst 3.0. Results: This study included eight aqueous humor samples from patients with cataract and diabetes and eight aqueous humor samples from age- and sex-matched patients with cataract alone. Four metabolites were found to significantly differ in the aqueous humor of patients with cataract and diabetes, relative to patients with cataract alone; these metabolites were glucose (higher in patients with diabetes), valine, lysine, and tyrosine (all lower in patients with diabetes). Aminoacyl-tRNA biosynthesis was presumed to be involved in the metabolic differences observed in patients with cataract, according to diabetes status. Conclusions: The amino acid metabolic profile in the aqueous humor differed among patients with cataract, according to diabetes status. Disturbance of amino acid metabolism in the aqueous humor may be related to cataract formation in patients with diabetes.